Graphic Materials as Catalyst in Reading Comprehension - Samuel S. Poliden (JPAIR Institutional Research Journal)
The study embarked on graphic materials as a catalyst in reading comprehension. Unknown to many, graphic materials are effective media in teaching the language. The study was conducted in 2010 to Bachelor of Science in Applied Statistics students at Benguet State University, La Trinidad, Benguet, Philippines. A 50-item test which consisted of comprehension of tables, graphs/charts, instructions, diagrams, pictorial illustrations, maps and notices/common signs was administered to determine their comprehension level with 10 items each. The test on graphic materials was taken from various local and national reading materials. Results showed that the most difficult task to comprehend by the respondents was the tables while instructions were the easiest. A significant difference was noted in the performance of the students as influenced by their year level. Based on the result of the study, it is recommended that any authentic material should be used in teaching the language. Language teachers should also utilize any graphic materials, multiple media, art, multidisciplinary thematic units, and even games in designing classroom tasks to promote reading comprehension skills. They should likewise provide interesting language lessons using newspapers, magazines or any graphic materials as input in developing comprehension skills.